A case of primary chylous ascites resolved within 4 months by exclusive breast-feeding - Kurugöl, Zafer; Çoğulu, Özgür; Kavaklı, Kaan (The Turkish Journal of Pediatrics, 2000)
Chylous ascites is a rare disease in infancy. A two-month-old male infant was admitted to the Department of Pediatrics with chylous ascites. No cause was found throughout the investigation period. The baby recovered spontaneously through breast-feeding without any specific treatment and chylous ascites disappeared at the age of six months.